A Case Report and Genetic Characterization of a Massive Acinic Cell Carcinoma of the Parotid with Delayed Distant Metastases. (3rd April 2013) - Nichols, Anthony C.; Chan-Seng-Yue, Michelle; Yoo, John; Agrawal, Sumit K.; Starmans, Maud H. W.; Waggott, Daryl; Harding, Nicholas J.; Dowthwaite, Samuel A.; Palma, David A.; Fung, Kevin; Wehrli, Bret; MacNeil, S. Danielle; et al.
Abstract : We describe the presentation, management, and clinical outcome of a massive acinic cell carcinoma of the parotid gland. The primary tumor and blood underwent exome sequencing which revealed deletions in CDKN2A as well as PPP1R13B, which induces p53. A damaging nonsynonymous mutation was noted in EP300, a histone acetylase which plays a role in cellular proliferation. This study provides the first insights into the genetic underpinnings of this cancer. Future large-scale efforts will be necessary to define the mutational landscape of salivary gland malignancies to identify therapeutic targets and biomarkers of treatment failure.